Women’s views and experiences of two alternative consent pathways for participation in a preterm intrapartum trial: a qualitative study - Sawyer, Alexandra; Chhoa, Celine; Ayers, Susan; Pushpa-Rajah, Angela; Duley, Lelia (BioMed Central, 2017)
Background The Cord Pilot Trial compared alternative policies for timing of cord clamping at very preterm birth at eight UK hospitals. In addition to standard written consent, an oral assent pathway was developed for use when birth was imminent. The aim of this study was to explore women’s views and experiences of two alternative consent pathways to participate in the Cord Pilot Trial.